Efficacy of immune checkpoint inhibitors in older patients with non-small cell lung cancer: Real-world data from multicentric cohorts in Canada and France. Issue 5 (June 2020) - Elkrief, Arielle; Richard, Corentin; Malo, Julie; Cvetkovic, Lena; Florescu, Marie; Blais, Normand; Tehfe, Mustapha; Messaoudene, Meriem; Gagné, Andréanne; Orain, Michele; Medjebar, Soleine; Wan-Chow-Wah, Doreen; et al.
Abstract: Background: Age-related immune remodelling is thought to be associated with resistance to immune checkpoint inhibitors (ICIs) in cancer. Patients older than 70 years, representing >50% of the population with non-small cell lung cancer (NSCLC) according to SEER database, are underrepresented in clinical trials exploring ICIs. The objective of this study was to determine if patients with NSCLC older than ≥70 years had inferior clinical outcomes with ICIs. Methods: We conducted a retrospective analysis of 381 patients treated with anti-PD-(L)1 ICI for advanced NSCLC at the Dijon Cancer Center ( n  = 177), University of Montreal Hospital ( n  = 106) and Quebec Heart and Lung Institute ( n  = 98). Age was considered as a categorical variable. Patients' baseline characteristics were compared using the Chi-squared test. Survival curves were estimated by the Kaplan-Meier method and compared with the Log-rank test in a univariate analysis. Multivariate cox regression model was used to determine hazard ratios and 95% confidence intervals for progression-free survival (PFS) and overall survival (OS) between the groups, adjusting for other clinicopathologic features. Results: Among 381 patients included, 335 (88%) received ICI after platinum chemotherapy. The median age was 66 (range 37–89) and 33% were older than 70 years of age. Considering age as a categorical variable, differences in age were not associated with PFS or OS. Subgroup analysis and multivariate cox regression did not reveal significant interaction of age with outcomes. ECOG performance status was the only significant factor in the three cohorts. Conclusions: Unlike previously described in the era of chemotherapy, age was not associated with outcomes in NSCLC patients treated with ICI.